Optimalisasi Manajemen Kelas untuk Membangun Lingkungan Belajar yang Kondusif - Ardiansyah, Achmad; Rifai, Dede Syukrillah; Yahya, Aliya Izet Begovic (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study aims to identify and analyze optimal classroom management strategies to enhance students' learning awareness through a literature review approach. A qualitative descriptive method was employed by examining various relevant sources, including books, scholarly journals, and previous research related to classroom management and learning motivation. The findings indicate that effective classroom management encompasses four key dimensions: (1) physical arrangement of the classroom to support comfort, (2) strengthening the teacher's role as a facilitator, (3) implementation of communicative and participatory interactions, and (4) the establishment of a positive and disciplined classroom culture. These strategies significantly contribute to increasing student engagement and learning awareness. The study also identifies both internal (teachers and students) and external (curriculum, facilities, parental support, and classroom climate) factors that either support or hinder classroom management. The main contribution of this study lies in formulating a holistic approach to classroom management by integrating technical and interpersonal aspects as the foundation for fostering students’ learning awareness.